A liver-fat crosstalk for iron flux during healthy beiging of adipose tissue - Jinying Yang; Limin Shi; Anna L. Cubito; James F. Collins; Zhiyong Cheng (Autophagy Reports)
Beiging of adipocytes is characteristic of a higher number of mitochondria, the central hub of metabolism in the cell. However, studies show that beiging can improve metabolic health or cause metabolic disorders. Here we discuss a liver-fat crosstalk for iron flux associated with healthy beiging of adipocytes. Deletion of the transcription factor FoxO1 in adipocytes (adO1KO mice) induces a higher iron flux from the liver to white adipose tissue, concurrent with augmented mitochondrial biogenesis that increases iron demands. In addition, adO1KO mice adopt an alternate mechanism to sustain mitophagy, which enhances mitochondrial quality control, thereby improving mitochondrial respiratory capacity and metabolic health. However, the liver-fat crosstalk is not detectable in adipose Atg7 knockout (ad7KO) mice, which undergo beiging of adipocytes but have metabolic dysregulation. Autophagic clearance of mitochondria is blocked in ad7KO mice, which accumulates dysfunctional mitochondria and elevates mitochondrial content but lowers mitochondrial respiratory capacity. Mitochondrial biogenesis is comparable in the control and ad7KO mice, and the iron influx into adipocytes and iron efflux from the liver remain unchanged. Therefore, activation of the liver-fat crosstalk is critical for mitochondrial quality control that underlies healthy beiging of adipocytes.